Carbon emissions disclosure: an overview of research in Indonesia - Nilasakti, Afifah Oki; Aryani, Y Anni; Setiawan, Doddy (Journal of Accounting and Investment, 2024)
Research aims: This research aims to find out the research’s development of carbon emissions disclosure topic in the Indonesia context.Design/Methodology/Approach: The method employed was charting the fields by Hesford et al. (2006) on some articles indexed by Sinta 2 and 3, as well as Scopus with research based in Indonesia. The articles were selected by criteria, obtaining 60 articles for further analysis.Research findings: The literature study’s results showcase that the carbon emission disclosure research trend in Indonesia has increased in the last five years. This trend was reviewed deeply through further discussions in terms of its factors influencing and consequences, theories and samples used. The major factors influencing carbon emission disclosure are profitability, firm size, and leverage. Moreover, carbon emission disclosure also affects firm value. Theoretical contribution/Originality: This study provides knowledge regarding existing carbon emission disclosures and opportunities for further research agenda, especially on empirical research.